THE EFFECT OF JOB SATISFACTION AND EMPLOYEE MOTIVATION ON EMPLOYEE LOYALTY (CASE STUDY OF PT KIMIA FARMA APOTEK IN SAM RATULANGI, MANADO) - Thanos1, Casie Angela (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Employee loyalty is a vital outcome of retaining employees. There are several ways to keep employees loyal, such as keeping employees satisfied with their job and motivated to do a better work. The objective of this research is to identify the effect of job satisfaction and employee motivation on employee loyalty. In this research, the population refers to the employees of Kimia Farma Apothecary of Sam Ratulangi Branch in Manado with sample size as many as 44 respondents. This research causal research and the data are gathered from using questionnaires and used multiple regression analysis. Result showed that job satisfaction and employee motivation variables have significant effect on employee loyalty simultaneously. Job satisfaction does not have significant partial effect on employee loyalty while employee motivation has partial significant effect on employee loyalty. Kimia Farma Apothecary should increase compensation and build good relationship between supervisor and employee to increase employee’s job satisfaction. Keywords: employee loyalty, job satisfaction, employee motivation.